Post-COVID depression and its multiple factors, does Favipiravir have a protective effect? A longitudinal study of indonesia COVID-19 patients. - Bumi Herman; Andrea Bruni; Ekachaeryanti Zain; Azhar Dzulhadj; Aye Chan Oo; Viwattanakulvanid (PLoS ONE, 2022)
Background Coronavirus disease (COVID-19) not only has a long-term effect on its survivors, it also affects their quality of life, including inducing depression as a possible manifestation of central nervous system disruption. Favipiravir shows promising efficacy as an antiviral drug for the treatment of COVID-19. However, its effect on the sequelae of COVID-19 has not been explored. Therefore, this study aims to assess the impact of Favipiravir and address the factors associated with post-COVID depression in Indonesia. Method This cohort study conducted a post-COVID-19 survey on Indonesian patients who were diagnosed by using real-time polymerase chain reaction (RT-PCR) and antigen tests until January 2022. An online questionnaire was distributed to obtain information on demographics, comorbidities, health behavior, symptoms, and treatment. The propensity technique was used to allocate the participants into the favipiravir and nonrecipient groups (1:1). The Patient Health Questionnaire-9 (PHQ-9) was used for outcome measurement. The cohort was followed up biweekly for 60 days after onset/diagnosis to determine the occurrence of depression. Cox regression analysis with an adjusted odds ratio and 95% confidence interval was used to estimate the effect of favipiravir on post-COVID-19 depression. Results The data included the information of 712 participants, of whom 18.54% had depression within 60 days after onset/diagnosis. Depression was higher in the nonrecipient group (21.06%) than in the favipiravir group (16.01%). After adjustment by other factors, favipiravir prescription was found to be associated with depression (aOR 0.488, 95% CI 0.339-0.701 p < 0.001). In accordance with the PHQ-9 subset, favipiravir exerted a significant protective effect against depressive mood and loss of interest. However, patients living alone were prone to experiencing loss of interest (aOR 2.253, 95% CI 1.329-3.818, p = 0.003). Conclusion The data obtained in this preliminary survey suggested that favipiravir may be useful for preventing post-COVID depression. However, further study is needed. Moreover, the provision of mental health support, particularly to those who live alone, must be ensured. Trial registration Registry NCT05060562.